Human Resource Authority and Professionalization within the Jakarta Metropolitan Police (Polda Metro Jaya): A Normative Legal Analysis of Institutional Reform in the Indonesian National Police - Laksito Ari Kusuma; Rasman Habeahan; Abu Nawas (BULETIN ADALAH, 2026)
The Indonesian National Police (Polri) plays a strategic role in maintaining public order, enforcing the law, and delivering protection and public services as mandated by the 1945 Constitution of the Republic of Indonesia and Law No. 2 of 2002 concerning the Indonesian National Police. Professionalism within the police institution constitutes a fundamental prerequisite for fulfilling these constitutional functions, particularly in the jurisdiction of the Jakarta Metropolitan Police (Polda Metro Jaya), which faces highly complex legal and socio-political challenges. This study examines (1) the development of human resources (HR) within Polda Metro Jaya in fostering police professionalism and (2) the role of law enforcement processes in strengthening institutional HR capacity to enhance professional standards. The research employs a normative legal method using statutory and conceptual approaches to analyze regulatory frameworks, institutional policies, and professional ethics standards governing police conduct. The findings indicate that human resource development represents a critical pillar in advancing institutional professionalism, improving public service quality, and reinforcing public trust. Although adequate legal foundations and internal regulatory mechanisms are in place, the implementation of HR development at Polda Metro Jaya continues to face structural and cultural challenges. These include inconsistencies in ethical enforcement, limitations in professional capacity building, and resistance to organizational cultural transformation. This study argues that sustainable and integrity-based HR reform is essential to strengthening police professionalism and institutional legitimacy. The research contributes to the discourse on police reform by emphasizing the centrality of normative governance, ethical accountability, and organizational culture in achieving a professional and publicly trusted law enforcement institution. Keywords Jakarta Metropolitan Police; Police Professionalism; Human Resource Development; Police Ethics; Institutional Reform